2022
DOI: 10.1093/plcell/koac253
|View full text |Cite
|
Sign up to set email alerts
|

WRKY53 negatively regulates rice cold tolerance at the booting stage by fine-tuning anther gibberellin levels

Abstract: Cold tolerance at the booting stage (CTB) is a major factor limiting rice (Oryza sativa L.) productivity and geographical distribution. A few cold-tolerance genes have been identified, but they either need to be overexpressed to result in CTB or cause yield penalties, limiting their utility for breeding. Here, we characterize the function of the cold-induced transcription factor WRKY53 in rice. The wrky53 mutant displays increased CTB, as determined by higher seed setting. Low temperature is associated with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…This can be achieved by the following ways: (1) It can be mediated by biased R‐loops overlapping TFs, such as OsERF101 , OsWRKY53 and bHLH144 , which can regulate gene transcription in response to COLD through the regulatory network. OsWRKY53 functions as a negative regulator at the rice booting stage under COLD (Tang et al ., 2022), while our preliminary result showed that it can act as a positive regulator at the rice seedling stage of rice under COLD (Fig. 4c), indicating that functions of OsWRKY53 in COLD responses may be developmental stage‐dependent.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This can be achieved by the following ways: (1) It can be mediated by biased R‐loops overlapping TFs, such as OsERF101 , OsWRKY53 and bHLH144 , which can regulate gene transcription in response to COLD through the regulatory network. OsWRKY53 functions as a negative regulator at the rice booting stage under COLD (Tang et al ., 2022), while our preliminary result showed that it can act as a positive regulator at the rice seedling stage of rice under COLD (Fig. 4c), indicating that functions of OsWRKY53 in COLD responses may be developmental stage‐dependent.…”
Section: Discussionmentioning
confidence: 75%
“…OsWRKY53 has recently been reported to negatively regulate chilling stress at the rice booting stage (Tang et al, 2022), while it had positive roles in the regulation of COLD response at the seedling stage after examining changes in OsWRKY53 expression and R-loop abundance using the same reported transgenic lines ( Figs 4c, S22). According to GRNs constructed, we identified 3953 DEGs (Fig.…”
Section: (B)mentioning
confidence: 97%
“…Meanwhile, the expression of DEGs involved in GA and JA hormone pathways were also induced and upregulated during differentiation phase, particular genes encoding LOX3 rate‐limiting enzyme in JA biosynthesis pathway and GA3ox key enzymes in GA 1 and GA 3 biosynthesis (Figures 8d–f and 9b,c). Genes LOX3 and GA3ox are key factor in JA and GA content, which regulate plant development (Jiao et al, 2018; Tang et al, 2022). Therefore, rapid development of spike and floret primordia was an important environment effect by the IPS treatment: although the 41 MYB and 19 NAC‐related TFs were significantly upregulated in the IPS treatment, only the TaGAM1‐6A TFs (MYB) was predicted to interact with TaHSP70‐4A.1 and TaHSP70‐8, which then interacted with JA pathway‐related genes TaMFP2‐4A, TaOPR‐7B.3, TaOPCL1‐3A.1 (Figure 10b).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the expression of DEGs involved in GA and JA hormone pathways were also induced and upregulated during differentiation phase, particular genes encoding LOX3 rate-limiting enzyme in JA biosynthesis pathway and GA3ox key enzymes in GA 1 and GA 3 biosynthesis (Figures 8d-f and 9b,c). Genes LOX3 and GA3ox are key factor in JA and GA content, which regulate plant development (Jiao et al, 2018;Tang et al, 2022) interact with TaHSP70-4A.1 and TaHSP70-8, which then interacted with JA pathway-related genes TaMFP2-4A, TaOPR-7B.3, TaOPCL1-3A.1 (Figure 10b). Thus, in the DEGs analysis between treatments during differentiation phase we worked out rapid response of spike to abiotic stresses by activation of MYB TFs (TaGAM1-6A), genes HSP70 and genes related to JA biosynthesis, which improved assimilates accumulation and then accelerated growth and development of spike (Figure 10b).…”
Section: Architecture Of Gene Regulatory Network Realising the Maximu...mentioning
confidence: 99%
See 1 more Smart Citation